Fat Embolism as a Rare Complication of Large-volume Liposuction in a Plastic Patient - Xiaoliang Fu; Shang Gao; Zhenyu Hu; Yadong Guo; Jifeng Cai (Wolters Kluwer Medknow Publications, 2015)
Fat embolism is a dreaded complication in of procedures of multiple disciplines including plastic surgery. As the popularity of liposuction increases, cases of pulmonary embolism after liposuction are increasingly reported. However, documents of cerebral embolism after liposuction are rarely presented. The degree of disability with respect to Fat fat Embolism embolism Symdrome syndrome (FES) is a Gordian Knot in the evaluation of legal medicine. Therefore, it is of great significance for us to that we report the case of a 30-year-old woman who underwent a large-volume liposuction that resulted in serious complications, especially cerebral embolism. Untypical symptoms of fat embolism hamper the clinical diagnosis, particularly after a surgical procedure such as liposuction. Such a seldom-seen case would easily trigger medical disputes, especially in countries like China suffering increasing claims of medical malpractice and, medical negligences and lawsuits. Detailed descriptions of this case are presented below along with the discussion of the clinical symptoms and the diagnostic approaches to fat embolism.